New mountain populations. Migrants and the actractiveness of Alpine territories - Gilli, Monica (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
The paper is dedicated to the analysis of the relationship between migrants and local development in mountain areas. The aim is to compare two different mountain realities: Alto Adige, in the Eastern Alps, and the metropolitan city of Turin, in the Western Alps, in order to highlight the capacity of the two territories to intercept and attract migrants arriving in Italy. The analysis is part of the Horizon 2020 MATILDE project, which aims to assess the economic and social impact of migration on local development and territorial cohesion in European rural and mountain areas. The research was carried out during 2021 and is based on individual semi-structured online interviews with about twenty privileged actors (scholars or professionals) followed by three in-depth thematic focus groups in online mode involving a total of another twenty experts from both territories. The paper consists of four paragraphs: the first one frames the economic and territorial characteristics of the two case studies, which are very useful to understand the attractiveness of the two territories towards migrants (paragraph 2); paragraph 3 asks about the inclusive capacity of mountain territories and the fourth one about the most complex level of this inclusiveness, consisting in the development of a sense of citizenship and the practice of active citizenship. Conclusions follow.